An impacted tibial plateau fracture in an adolescent diver: a case report - Edler, J. R.; Games, K. E.; Eberman, L. E.; Kahanov, L. (International Journal of Athletic Therapy & Training, 2016)
The tibial plateau is a critical load-bearing surface in humans. Although tibial plateau fractures represent only 1% of all fractures, proper management by all members of the health care team, including athletic trainers, physicians, and physical therapists, is required for successful patient outcomes. A 14-year-old national-level competitive female diver injured her right knee during the precompetition warm-up period. Upon evaluation by an athletic trainer, the patient was referred for imaging and examination by a physician. She was seen by an orthopedic surgeon for consultation. The patient elected for a surgical repair of the tibial plateau fracture. Following surgery she underwent an 11-week comprehensive therapeutic exercise program with athletic trainers and physical therapists. The patient`s return-to-play progression included dry land activities, platform diving, 1-m springboard diving, and 3-m springboard diving. The patient has successfully returned to competitive diving. Proper identification of tibial fractures can be difficult considering their low occurrence in youth and their similar clinical presentation to more common youth injuries such as anterior cruciate ligament ruptures. Clinicians providing immediate on-site medical care should be thorough in their clinical exam including palpation and axial loading of the joint.